Guidance and Counseling Services in Improving the Psychological Well-Being Young Prisoners - Akmil Rahmi; Marjohan Marjohan; Daharnis Daharnis (Fakultas Ilmu Pendidikan UNP)
Young prisoners need guidance, direction and assistance from parents and the immediate environment in order to develop into more mature. Some of the problems experienced by young prisoners are not able to accept themselves and difficult circumstances to direct behavior so that affects the psychological well-being. Psychological well-being is a condition in which an individual can accept themselves and be able to rise from its current state. This article discusses the basic concepts of psychological well-being and the importance of guidance and counseling services.